In the aftermath of the earth summit: responsible global action for the 21st century: comments and documents (Stiftung Entwicklung und Frieden Bonn-BudDE, 1993)
Describes what is being done and what is still to be done after the 'Rio Summit'. Looks at issues such as human beings at the centre of concerns for sustainable development; environmental policy as part of global development; and, heading for a new and fair partnership. Includes documents from the UN Conference on Environment and Development and the International NGO Forum.
DC